IMPACT OF SELECTED MACROECONOMIC INDICATORS ON THE WARSAW STOCK EXCHANGE INDEX – THE FOOD INDUSTRY - Firlej Krzysztof; Marcin Stanuch (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The primary objective of this study is to analyze the macroeconomic conditions influencing the operation and development of the food industry in Poland, with a particular focus on their role in shaping the WIG-Food index. This research stems from current market observations, recognized constraints affecting the industry’s performance, and investment decisions made in this sector. The study examines key macroeconomic indicators deemed most relevant by the authors and seeks to establish a regression model to assess their impact on the WIG-Food stock exchange index. The research period spans from 2014 to 2023 and includes an analysis of factors such as Gross Domestic Product (GDP), inflation, retail sales, and industrial production. The correlation analysis revealed a moderate relationship between selected macroeconomic indicators and the WIG-Food index. Furthermore, the causality analysis indicated that certain macroeconomic variables, including GDP, retail sales, and industrial production, significantly influence the stock exchange index. While the regression model effectively identified the key factor affecting the dependent variable, its limited explanatory power suggests the necessity of incorporating additional variables for a more comprehensive analysis.